Improvement of solubilization and uptake of dietary antioxidants in human hepatocellular liver carcinoma (HepG2) cell line (PDNP4) - Jaswir, Irwandi; Nagao, Akihiko (2009)
Antioxidant activity of carotenoids may shift into prooxidant activity, depending on several factors, such as oxygen tension, carotenoid concentration, and interactions with other antioxidants. This study was conducted to prepare DMEM culture medium containing high concentrations of lutein and β-carotene for evaluation of the anti- and pro-oxidant activities and their dependency on concentrations of the carotenoids. We successfully developed a new method to prepare DMEM medium containing higher concentration of lutein and beta-carotene. In the new method, lutein and β-carotene were solubilized in 5% THF. However, the concentration of THF was then reduced almost completely through evaporation. THF concentration checking was done using a headspace gas chromatography. Using this evaporation method, results showed that medium containing up to 90μM could be obtained, compared to a maximum of 15uM of lutein by using a conventional method, while THF was reduced to a non-toxic level as low as 0.01%. This finding allowed the use of high concentrations of the carotenoids for antioxidative activity study. Cellular uptake and antioxidative activity in HepG2 cells of the carotenoids were examined under a wide range of their concentrations.